MECHANISMS OF ACTIVIZATION OF ECONOMIC RELATIONS OF REPRODUCTION OF THE INTERNAL RESOURCES OF THE REGION - E. Ostapenko (Вестник университета, 2019)
The process of reproduction of human capital at the regional level requires the development and implementation of a special set of mechanisms and instruments of territorial administration, adapted to the conditions of functioning and development of regional economic systems. The article substantiates the mechanisms for activating the economic relations of reproduction of the region’s internal resources. The process of reproduction of human capital has been highlighted as a priority area of regional economic policy. The target direction of financial and investment support for the process of generating human capital has been identified. The dynamic management of the interests of the subjects of the human capital reproduction process has been determined. The priority of institutional tools to revitalize the internal resources of the region has been defined.